2021
DOI: 10.1001/jamahealthforum.2021.1816
|View full text |Cite
|
Sign up to set email alerts
|

Physician Network Breadth and Plan Quality Ratings in Medicare Advantage

Abstract: This cross-sectional study examines the extent of narrow networks across Medicare Advantage, types of counties where they are common, enrollment in narrow network plans, and how networks are associated with star ratings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 6 publications
1
42
0
Order By: Relevance
“…What might be leading to these differences in care experiences for enrollees with ADRD? Prior work has found that MA beneficiaries tend to be admitted to lower quality hospitals, nursing homes, and home health agencies than those in TM, 32–34 and that MA networks are often narrow in nature 4,35,36 . While all beneficiaries in our study are enrolled in MA, narrow networks and other barriers to care such as prior authorizations may be an additional burden for beneficiaries with ADRD to navigate than healthier enrollees.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…What might be leading to these differences in care experiences for enrollees with ADRD? Prior work has found that MA beneficiaries tend to be admitted to lower quality hospitals, nursing homes, and home health agencies than those in TM, 32–34 and that MA networks are often narrow in nature 4,35,36 . While all beneficiaries in our study are enrolled in MA, narrow networks and other barriers to care such as prior authorizations may be an additional burden for beneficiaries with ADRD to navigate than healthier enrollees.…”
Section: Discussionmentioning
confidence: 73%
“…Prior work has found that MA beneficiaries tend to be admitted to lower quality hospitals, nursing homes, and home health agencies than those in TM, [32][33][34] and that MA networks are often narrow in nature. 4,35,36 While all beneficiaries in our study are enrolled in MA, narrow networks and other barriers to care such as prior authorizations may be an additional burden for beneficiaries with ADRD to navigate than healthier enrollees. Enrollees with dementia may also face challenges in selecting the right plan for them, leading to lower-rated care experiences.…”
Section: Discussionmentioning
confidence: 99%
“…One-third of Medicare Advantage enrollees are in plans with narrow physician networks, although only one-fifth of consumers feel positively about narrow networks when other options are presented . Conversely, 2 recent studies have found narrow networks to be associated with higher quality for Medicare Advantage plans . Medicare Advantage payment rates are unlikely to be a direct mechanism given that we controlled for HRR in all analyses, making all comparisons within regions where payment rates are the same.…”
Section: Discussionmentioning
confidence: 97%
“… 3 Conversely, 2 recent studies have found narrow networks to be associated with higher quality for Medicare Advantage plans. 25 , 26 Medicare Advantage payment rates are unlikely to be a direct mechanism given that we controlled for HRR in all analyses, making all comparisons within regions where payment rates are the same.…”
Section: Discussionmentioning
confidence: 99%
“…As highly rated MA contracts establish networks with highly rated providers, this suggests that provider networks are a pathway used by MA contracts to improve outcomes. 8,9 The findings should be interpreted within several limitations. There may be selection into highly rated MA contracts.…”
Section: Discussionmentioning
confidence: 99%